Empirical analysis of macroeconomic factors and Structural Adjustment Program (SAP) on agricultural output - Oluwatoyese Oluwapemi Oyetade; Shri Dewi Applanaidu; Oyetade Eunice Modupe (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
There has been many significant research efforts that have been devoted to understand the effects of macroeconomic factors on the agriculture sector in Nigeria. In addition to the macroeconomic factors, Structural Adjustment Programme (SAP) over the period 1981 to 2017 will be included into the scenario of this study to examine the effects of these factors on agricultural output in Nigeria. This paper employed co-integration analysis and multivariate Granger causality which is carried out using VECM approach to analyse the causal links among all the variables considered for estimation. The findings showed relationship that exists between the agricultural output which is the dependent variable and the independent variables. It also revealed the variations between the dependent and independent variables which are Gross Domestic Product (GDP) growth rate, interest rate, foreign direct investment (FDI), commercial bank loan on agriculture, SAP and inflation rate. In conclusion, commercial loan on agriculture, FDI, interest and inflation rate were macroeconomic variables that contributed to agricultural output in Nigeria within the period examined.